(untitled) (REMUNOM, 2023)
This study aimed to verify the role of the nurse in Primary Health Care in order to work on strengthening family and community ties in the inclusion of the mentally ill in society. Having as specific objectives: to identify which actions are aimed at strengthening family and community ties, verify the functionality of the psychosocial care network for users, understand the basic health rights of people with mental illnesses, in order to guarantee them, in addition to developing actions established in public policies, identifying the user care network. Throughout the article, we tried to clarify the importance of the nurse and the entire health team together with the support networks in reception for the inclusion of the mentally ill in the Basic Health Units. In the end, it was verified that the CAPS is a reference of psychosocial assistance, where it constitutes the main strategy of the psychiatric reform process.